2013
DOI: 10.1039/c3cc40620b
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced power conversion efficiencies in bulk heterojunction solar cells based on conjugated polymer with isoindigo side chain

Abstract: A novel conjugated side-chain polymer (PBDT-TID), based on benzo[1,2-b:4,5-b']dithiophene (BDT) and isoindigo (ID) moieties, was designed and synthesized. The new polymer exhibited excellent microphase separation in active layers. Bulk heterojunction polymer solar cells fabricated from PBDT-TID and PC61BM showed promising power conversion efficiencies of 5.25% and 6.51% using conventional and inverted device structures, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 25 publications
(31 reference statements)
0
29
0
Order By: Relevance
“…Many IDbased polymers exhibited intense and broad absorption, which is beneficial to achieving high photovoltaic performances in PSCs [23]. And the sidechain ID unit has been reported by our group for the first time, wherein the inverted device based on PBDT-TID obtained a high PCE of 6.51% [24]. Benzodithiophene (BDT) unit is widely used in photovoltaic devices because of its symmetrical planar conjugated structure and excellent photovoltaic performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many IDbased polymers exhibited intense and broad absorption, which is beneficial to achieving high photovoltaic performances in PSCs [23]. And the sidechain ID unit has been reported by our group for the first time, wherein the inverted device based on PBDT-TID obtained a high PCE of 6.51% [24]. Benzodithiophene (BDT) unit is widely used in photovoltaic devices because of its symmetrical planar conjugated structure and excellent photovoltaic performance.…”
Section: Introductionmentioning
confidence: 99%
“…M1) and (5,5'-(2,5-bis((2-ethylhexyl)oxy)-1,4-phenylene) bis(thiophene-5,2-diyl))bis(trimethylstannane) (M3) were prepared according to literature procedures [24][25][26].…”
Section: Experimental Section 21 Materialsmentioning
confidence: 99%
“…Thus, the isoindigo core was modified with a thiophenecarbaldehyde fragment using Stille coupling followed by Horner-Wadsworth-Emmons reaction to give corresponding monomer (58). 109 Then repeated Stille polycondensation afforded the desired polymeric compound (59) …”
Section: Scheme 26mentioning
confidence: 99%
“…As shown in Figure 1, two-dimensional (2-D) conjugation by vinylene linkage, such as thienylenevinylene [16], bi(thienylene-vinylene) [17], phenothiazine-vinylene [18], triphenylamine-vinylene [19], and terthiophene-vinylene [20], has proven to be a successful strategy to enhance lightharvesting ability, charge mobility and self-assembly, and adjust molecular energy levels to meet the requirements of PSCs [17,20,21]. Moreover, Tan and co-workers reported that a series of 2-D conjugated polymers incorporating different thienylene-vinylene derivatives with BDT building blocks, such as PTG1 [22] and PBDT-TID [23], not only attracted much interest but also demonstrated an effective strategy to extend the absorption range and down-shift the HOMO energy level. On the other hand, Li and co-workers reported that introduction of strong electro-withdrawing groups, such as pyrrolo [3,4-c]pyrrole-1,4-dione (DPP), in the 2-D conjugated polymers broadens the spectral absorption via the random polymerization [24].…”
Section: Introductionmentioning
confidence: 99%